ilex subsp. ballota) DE MONTE BAJO TRAS DISTINTAS INTENSIDADES DE RESALVEO SEIS AÑOS DESPUÉS DEL FUEGO. RESULTADOS PRELIMINARES - GONZÁLEZ-OCHOA, A I; Lopez, F; DE LAS HERAS, J (III Congreso Forestal Español, 2001)
In a post-fire coppice forest of Quercus ilex different thinning intensities (0%, 53%, 88% and 100%) were carried out in order to evaluate their effects on the dynamic of the forest. The following spring after treatments, there were not significative differences for no thinning intensity on diameter relative growth but, on the contrary, there were differences for height relative growth between control plots and 88% thinning intensity. The higher resprouting percentage is reached for the treatment of 88% thinning intensity, while the lowest is registered in the control plots. Finally, the specific leaf area is higher for resprouters in control plots than in the treated ones. K.W.:
Keywords: Coppice forest; resprouting; thinning

Micorrización de plantas de PINUS HALEPENSIS, PINUS PINASTER Y QUERCUS ILEX SUBSP. BALLOTA PARA REPOBLACIÓN DE ZONAS INCENDIADAS DE ESCASA REGENERACIÓN NATURAL. - GÓMEZ-SÁNCHEZ, E; GONZÁLEZ-OCHOA, A I; TORRES, P; DE LAS HERAS, J; SIMARRO, E (III Congreso Forestal Español, 2001)
In order to obtain plant of good quality for afforestation of burned zones, seedlings inoculation has been carried out in nursery with different species of ectomycorrhizal fungi, using different inoculation techniques. The inoculated seedlings belong to three Mediterranean tree species with high colonizer capability of burned zones: Pinus halepensis, Pinus pinaster and Quercus ilex subsp. ballota. All of them were produced in container. The fungi used were: Lactarius deliciosus, L. sanguifluus, Suillus bellinii, S. collinitus, S. mediterraneensis and Pisolithus tinctorius for pine species; and Tuber melanosporum in the case of holm-oak. For Pinus inoculation it was made mycelial slurries and spore suspensions. For Quercus inoculation it was produced spore suspension. The experiment was carried out in two different nurseries, and it was evaluated the seedling heights and the mycorrhization percentage obtained using several parameters. Our results let optimize the application of mycorrhizal techniques in nurseries in order to produced mycorrhized plants with commercial aims.
Keywords: ectomycorrhizal fungi; Inoculation; mediterranean burned forests